2015
DOI: 10.1080/14459795.2015.1062532
|View full text |Cite
|
Sign up to set email alerts
|

The role of homework in exposure-based CBT outcome for problem gambling

Abstract: Assigning homework is a key component of cognitive behavioural therapy (CBT) and engagement of homework has been shown to predict CBT outcomes for a range of disorders. However, no previous study has empirically examined directly the effect of homework engagement on CBT outcome for problem gambling (PG). To address this gap in the literature this study examined the role of homework along with two non-specific variables (treatment credibility and expectancy), and their prediction of short-term outcome in the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 43 publications
0
5
0
1
Order By: Relevance
“…x / Petry (2012) x x x Riley (2015) x Stinchfield et al (2008) x Ladouceur, et al (2009) x Stinchfield et al (2008) x Employment status Alvarez-Moya et al (2011) x 6 0% Aragay et al (2015) x Ingle et al (2008) x Jimenez-Murcia et al (2015) x x Ladouceur, et al (2009) x Stinchfield et al (2008) x Ethnicity Ingle et al (2008) Stinchfield et al (2008) x Gender (male) Aragay et al (2015) x 9 33% Grant, et al (2009) x Hodgins, et al (2001) x (2012) x + Stinchfield et al (2008) x Riley (2015) x Stinchfield et al (2008) x Illegal behaviours (presence of)/ Legal problems Aragay et al (2015) x 2 50% Ladouceur, et al (2009) x Smith et al (2011) x Stinchfield et al (2008) x Weinstock, et al (2007) x Gambling-related client characteristics Age of disordered gambling onset Ramos-Grille et al (2015) x 1 0% …”
mentioning
confidence: 99%
“…x / Petry (2012) x x x Riley (2015) x Stinchfield et al (2008) x Ladouceur, et al (2009) x Stinchfield et al (2008) x Employment status Alvarez-Moya et al (2011) x 6 0% Aragay et al (2015) x Ingle et al (2008) x Jimenez-Murcia et al (2015) x x Ladouceur, et al (2009) x Stinchfield et al (2008) x Ethnicity Ingle et al (2008) Stinchfield et al (2008) x Gender (male) Aragay et al (2015) x 9 33% Grant, et al (2009) x Hodgins, et al (2001) x (2012) x + Stinchfield et al (2008) x Riley (2015) x Stinchfield et al (2008) x Illegal behaviours (presence of)/ Legal problems Aragay et al (2015) x 2 50% Ladouceur, et al (2009) x Smith et al (2011) x Stinchfield et al (2008) x Weinstock, et al (2007) x Gambling-related client characteristics Age of disordered gambling onset Ramos-Grille et al (2015) x 1 0% …”
mentioning
confidence: 99%
“…El tratamiento cognitivo conductual es el que se ha demostrado más eficaz para el tratamiento de la adicción al juego (Petry et al, 2006;Sylvain et al, 1997;Tolchard & Battersby, 2013). El mismo que tiene en cuenta tanto los aspectos puramente conductuales, como la exposición a señales (Ashrafioun et al, 2012;Riley, 2015;Riley et al, 2011;Riley et al, 2018), y los aspectos cognitivos (Smith et al, 2013).…”
Section: Discussionunclassified
“…It is possible that this relationship plays a central role in determining the observed outcomes. In a naturalistic study involving help-seeking problem gamblers, Riley (2015) found that engaging in homework has a strong association with immediate and short-term outcome.…”
Section: Discussionmentioning
confidence: 99%